2017
DOI: 10.1097/nan.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Instituting Vincristine Minibag Administration

Abstract: The first fatal incident of wrong-route administration of vinca alkaloids occurred in 1968. Initial recommendations for practice change occurred in 2005. In 2012, 54% of oncology treatment sites had changed their practice. The authors' institution has developed a safe, adaptable, and consistent process to prepare, deliver, and administer vinca alkaloids by means of a minibag delivery. A multidisciplinary team, including representatives from the nursing and pharmacy departments, reviewed the literature and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…The other studies were published in different health journals. 3,[13][14][15][16]19,21,[24][25]31,33,43,[36][37]39,42,47,[49][50] The safety of cancer drug administration in adults, children and young people in hospitals, [3][4][6][7][13][14][15][16][17][18][19][20][21][22]27,33,[35][36][40][41]44,[47][48][49][50]52 outpatient clinics, [3][4][5][16][17][18][19...…”
Section: /18mentioning
confidence: 99%
See 4 more Smart Citations
“…The other studies were published in different health journals. 3,[13][14][15][16]19,21,[24][25]31,33,43,[36][37]39,42,47,[49][50] The safety of cancer drug administration in adults, children and young people in hospitals, [3][4][6][7][13][14][15][16][17][18][19][20][21][22]27,33,[35][36][40][41]44,[47][48][49][50]52 outpatient clinics, [3][4][5][16][17][18][19...…”
Section: /18mentioning
confidence: 99%
“…In order to avoid permanent sequelae and unnecessary tragic deaths as a result of intrathecal administration of vinca alkaloids, several procedures are recommended in institutions where intrathecal medications are administered: handling vincristine in an infusion bag (minibags), eliminating the risk of exchange with intrathecal syringes; labeling the infusion bags with vincristine preparations with an alert (for intrathecal use only); establishing a differentiated procedure for intrathecal drug administration, in another location and/or at times or days different from the intravenous medications (if this procedure is not possible, as for people receiving medication via both routes, a procedure must be performed so that intravenous vincristine is not dispensed until the confirmation of the end of intrathecal administration or vice versa); not using an infusion pump to infuse intrathecal vincristine (higher likelihood of leakage). 4,13 In the CTX administration phase, the following is recommended double-check by nurses for patient identification; check if the patient is wearing the identification bracelet with at least two identifiers; check for allergies to the drugs to be administered; identify drug name, dose, volume, route of administration, start and end date; check the appearance of the drug; put the signature and stamp on the prescription of all professionals (doctor, nurse and pharmacist); analyze if the CTX scheme was observed (adequate time since last cycle); identify treatment-related toxicity (if applicable); confirm if there are supportive medications; recalculate CTX doses; compare diluted drug labels with prescription and antineoplastic regimen; check for specific prescribed sequence; guide the patient verbally and deliver in writing (manual, folder); monitor the patient before, during and after drug administration; perform monitoring after CTX administration, including adherence, toxicity and complications. [4][5][15][16][17][18][19][20][21]24,26,32,[40][41][42]44,46,48,50 Studies have shown that the implementation of evidence-based care protocols improves care, organizes health services with the establishment of flows, and that they are imperative to improve the quality of care and patient safety.…”
Section: /18mentioning
confidence: 99%
See 3 more Smart Citations